Persepsi Guru dan Kesiapan Kompetensi Digital Berbasis Kerangka TPACK di SD Muhammadiyah 02 Bendan Pekalongan - Susanti, Indra; Puji Astuti, Wiewiek; Soleh, M Nur; Nahdhiyatunnisak; Murtiyasa, Budi (Edukasiana: Jurnal Inovasi Pendidikan, 2026)
Digital transformation in education demands teachers to master integrated competencies encompassing technology, pedagogy, and content. This study aims to analyze teachers' perceptions and digital competency readiness at SD Muhammadiyah 02 Bendan, Pekalongan City, using the Technological Pedagogical Content Knowledge (TPACK) framework. A descriptive qualitative approach was employed with purposive sampling involving five participants. Data were collected through semi-structured in-depth interviews, classroom observations, and documentation studies, then analyzed using the Miles, Huberman, and Saldana model. Results reveal an asymmetric digital competency profile: teachers demonstrate high self-efficacy in basic Technological Knowledge (TK) dimensions (software score 2.50; hardware 2.42), yet face significant barriers in Technological Pedagogical Knowledge (TPK), particularly in LMS adoption (score 1.75). A paradox emerges in TPACK integration, where strong pedagogical motivation is constrained by technical skill deficits in content production. Core barriers are predominantly psychological and cultural rather than technical. This study concludes that teacher training programs should be designed strength-based, leveraging existing pedagogical motivation as an entry point for contextually relevant technical competency development.